The Fornax Deep Survey (FDS) with the VST XI. The search for signs of preprocessing between the Fornax main cluster and Fornax A group - Su AH; Salo H; Janz J; Laurikainen E; Venhola A; Peletier RF; Iodice E; Hilker M; Cantiello M; Napolitano N; Spavone M; Raj MA; et al. (EDP SCIENCES S A, 2022)
Context. Galaxies either live in a cluster, a group, or in a field environment. In the hierarchical framework, the group environment bridges the field to the cluster environment, as field galaxies form groups before aggregating into clusters. In principle, environmental mechanisms, such as galaxy-galaxy interactions, can be more efficient in groups than in clusters due to lower velocity dispersion, which lead to changes in the properties of galaxies. This change in properties for group galaxies before entering the cluster environment is known as preprocessing. Whilst cluster and field galaxies are well studied, the extent to which galaxies become preprocessed in the group environment is unclear.
Aims. We investigate the structural properties of cluster and group galaxies by studying the Fornax main cluster and the infalling Fornax A group, exploring the effects of galaxy preprocessing in this showcase example. Additionally, we compare the structural complexity of Fornax galaxies to those in the Virgo cluster and in the field.
Methods. Our sample consists of 582 galaxies from the Fornax main cluster and Fornax A group. We quantified the light distributions of each galaxy based on a combination of aperture photometry, Sérsic+PSF (point spread function) and multi-component decompositions, and non-parametric measures of morphology. From these analyses, we derived the galaxy colours, structural parameters, non-parametric morphological indices (Concentration C; Asymmetry A, Clumpiness S; Gini G; second order moment of light M20), and structural complexity based on multi-component decompositions. These quantities were then compared between the Fornax main cluster and Fornax A group. The structural complexity of Fornax galaxies were also compared to those in Virgo and in the field.
Results. We find significant (Kolmogorov-Smirnov test p-value < α = 0.005) differences in the distributions of quantities derived from Sersic profiles (g' - r', r' - i', Re, and μ̄e,r'), and non-parametric indices (A and S) between the Fornax main cluster and Fornax A group. Fornax A group galaxies are typically bluer, smaller, brighter, and more asymmetric and clumpy. Moreover, we find significant cluster-centric trends with r' - i', Re, and (mu) over bar (e,r'), as well as A, S, G, and M20 for galaxies in the Fornax main cluster. This implies that galaxies falling towards the centre of the Fornax main cluster become fainter, more extended, and generally smoother in their light distribution. Conversely, we do not find significant group-centric trends for Fornax A group galaxies. We find the structural complexity of galaxies (in terms of the number of components required to fit a galaxy) to increase as a function of the absolute r'-band magnitude (and stellar mass), with the largest change occurring between -14 mag ≲​​​​​​​ Mr' ≲ - 19 (7.5 ≲ log10 (M*/M⊙) less than or similar to 9.7). This same trend was found in galaxy samples from the Virgo cluster and in the field, which suggests that the formation or maintenance of morphological structures (e.g., bulges, bar) are largely due to the stellar mass of the galaxies, rather than the environment they reside in.